Comparative analysis between overlapping and non-overlapping operation modes for the PWM buck converter using the three-state switching cell - Robles Balestero, Juan Paulo; Tofoli, Fernando Lessa; Seixas, Claudiner Mendes de; Torrico Bascope, Grover Victor [UNESP]; Mendes de Seixas, Falcondes Jose [UNESP] (Taylor & Francis Ltd, 2014)
This article presents a comparative study involving a buck converter derived from the three-state switching cell in both operation modes, i.e. non-overlapping and overlapping modes, since it is well known in literature that several advantages can be addressed to topologies based on this approach. In the case of the mentioned converter, only part of the load delivered to the load flows through the controlled switches, so that operation at high-current high-power levels is possible. Besides, the design of reactive elements such as very autotransformer and filter inductor is performed for twice the switching frequency, with consequent reduction of size, weight and volume. Another clear advantage is that the area for which the converter operates in continuous conduction mode is wider than that for the discontinuous conduction mode in comparison with the so-called classical non-isolated buck converter. The operation of the converter, which was previously proposed in literature, is analysed considering the aforementioned modes in terms of the efficiency, and similar approaches for the non-isolated dc-dc conversion are also investigated.
Keywords: dc-dc converter; buck converter; PWM; three-state switching cell